SYAWALAN TRADITION IN PEDURUNGAN SEMARANG AS LOCAL WISDOM IN THE PERSPECTIVE OF SOCIAL STUDIES EDUCATION - Lamiah, Jumaniyatu; Masrukhi; Gunawan (Universitas Negeri Medan, 2025)
Syawalan tradition is a form of local wisdom that contains social, cultural, and educational values that are closely related to the objectives of social studies education. Social studies education plays an important role in instilling an understanding of social interaction, cultural diversity, and values in community life. This study aims to analyze the meaning of local wisdom values in the Syawalan tradition in Pedurungan Semarang and its relevance in the perspective of social studies education. This research is expected to contribute to efforts to maintain and preserve the values of local wisdom in the tradition of Syawalan in Pedurungan Semarang as one of the nation’s identities, as well as realizing the purpose of social studies education is to form good citizens (good citizenship) in the life of society, nation, and state harmonious. This research uses a case study approach to analyze the meaning of the local wisdom value of the Syawalan tradition in Pedurungan, Semarang, from the perspective of social studies education. Syawalan tradition in Pedurungan Semarang is conducted after Eid al-Fitr, which has social, cultural, and religious values that can be learned in the context of education. The research method used is qualitative to explore the experience and meaning of the community towards the Syawalan tradition. The research location is in Pedurungan Tengah Urban Village, Pedurungan District, Semarang City. The data collection techniques used were observation, in-depth interviews, and documents.